The International Water Management Institute's work on climate change and possibilities for Myanmar: seeking solution for the measure of adaptation and mitigation against the impact - Inada, Yoshiaki (2012)
As water is perhaps the most important element in climate change adaption, in particular as related to agriculture, IWMI has focused considerable resources on the topic of climate change and has been at the forefront of climate change science as related to agricultural adaption in the developing world. IWMI's climate work has been focused on 1) better information to understand the impacts of climate change on farmers, 2) understanding the range of storage options-from natural wetlands, groundwater aquifers, and ponds to large scale dams-that can help farmers adapt to changing water supply as well as extreme events, and 3) understanding how changes in water governance can increase farmer options and improve outcomes. Of particular relevance is work conducted in the Mekong Delta on issues associated with changing salinity as a consequence of sea level rise, and a recent synthesis of the relationship between climate change, water and agriculture in the Mekong sub-region. This paper will highlight how existing work can be applied to the issues of Myanmar and promising directions for future work, especially as related to the Ayeyarwady Delta.